Interculturality: a challenge in teacher training - Monné Bellmunt, Alexandra; Porté Porté, Carles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Master of Education challenges students to design a proposal with the aim of promoting interculturality and thus responding to the different needs that they have perceived in the schools where they are carrying out their internships. An encourage range of proposals was presented, such as the creation of welcoming classrooms, the creation of language pairs, international school menus, second-hand markets, the reuse of leftover food as fertilizer for intergenerational gardens, and multilingual glossaries of keywords related to world-famous stories. Students’ proposals mainly focus on linguistic and gastronomic exchange, the reuse of resources, and family involvement and participation.